Bisphenol A is a carcinogen that induces lipid accumulation, peroxisome proliferator-activated receptor-γ expression and liver disease - Qasim Ismael, Layla; Abdulhameed, Ahmed Rashid; Yong, Yoke Keong; Abdullah, Muhammad Nazrul Hakim; Bahari, Hasnah; Tan, Jun Jie; Khoo, Boon Yin (Spandidos Publications, 2022)
Bisphenol (BP) A is an exogenous endocrine disruptor that mimics hormones closely associated with health complications, e.g., obesity and cancers. The present study aimed to evaluate the effects of BPA on human liver cells and tissue. The peroxisome proliferator‑activated receptor (PPAR)‑γ expression profile across tumour samples and paired normal tissue was first analysed using GEPIA. Subsequently, BPA‑treated liver THLE‑2 cell viability was evaluated using an MTT assay. Clusterin, PPARα and PPARγ gene expression in BPA‑treated THLE‑2 cells was assessed using GEPIA before validating the gene expression using real‑time PCR and analysing overall survival using TCGA data in GEPIA. Cytoplasmic lipid accumulation was examined in BPA‑treated THLE‑2 cells using Oil Red O staining, and liver tissue was examined using haematoxylin and eosin staining. Finally, cytochrome P450 (CYP) gene expression was assessed in BPA‑treated THLE‑2 cells using real‑time PCR. PPARγ is likely the primary nuclear receptor protein involved in lipid accumulation in THLE‑2 cells following BPA treatment and is associated with liver disease. THLE‑2 cells exposed to BPA showed a decrease in viability and lipid accumulation after 48 h treatment. Higher PPARγ gene expression was significantly associated with survival of patients with liver cancer, with an average survival time of <80 months. Haematoxylin and eosin‑stained sections showed notable disruption of the liver architecture in tissue exposed to BPA. Downregulated CYP1A1 and CYP1B1 gene expression implied that BPA‑treated THLE‑2 cells decreased capacity for carcinogen metabolism, while upregulated CYP2S1 gene expression exerted minimal cytotoxicity. The present study revealed that BPA served as a carcinogen, enhanced tumorigenesis susceptibility and may induce other types of liver disease.